Just-In-Time Simulation Training for Nasopharyngeal Specimen Collection During the SARS-CoV-2 Pandemic. Issue 1 (27th August 2022) - Carlson, Kristy J.; Klute, Lauren M.; Dowdall, Jayme R.; Pate, Samuel; Lyden, Elizabeth R.; Stobbe, Benjamin B.; Misra, Asit; Barnes, Christie A.
Abstract : Introduction: Rapid and accurate detection of the novel coronavirus using a nasopharyngeal specimen requires training for professionals who may have limited experience. To respond to the urgent need, an interprofessional team created a just-in-time (JIT) module to provide only what was needed, precisely when needed, and rapidly deployed training sessions to a large group of health professionals. Methods: In April and May 2020, health professionals from the hospital, ambulatory clinics, and public health attended training. Procedural comfort/knowledge and perception of the training were assessed with pre-survey and post-survey. Results: Comfort level in collecting a nasopharyngeal specimen among participating health professionals increased from 2.89 (n = 338) on the pre-survey to 4.51 (n = 300) on the postsurvey on a 5-point scale. Results revealed a significant difference ( P < .01) between pre–post knowledge questions regarding the correct angle and depth of the swab to obtain an adequate sample from the nasopharynx. Discussion: This study demonstrates that a JIT intervention can improve knowledge and comfort regarding the nasopharyngeal swab procedure. In preparation for the prevention and mitigation of future viral outbreaks (ie, coronavirus and influenza), educators should consider creating JIT skills training for health care professionals who may be deployed to assist in mass testing efforts.